FACTORS INFLUENCING ADAPTATION OF INNOVATIONS IN SMALL RUMINANT PRODUCTION IN THE TRC3 REGION IN TURKEY - acıbuca, veysi; bostan budak, dilek (Emirates Journal of Food and Agriculture, 2021)
This study investigated the socio-economic factors affecting the adoption of innovation in small ruminant production in TRC3 region in Turkey. Stratified random sampling technique was used to select 366 small ruminant farmers from the region. Semi-structured questionnaire was used to collect main data for the study. Data collected were analyzed using descritive statistics, t-tests and multiple linear regression analysis. Results of the study showed that the farmers had a mean age of 45,8 years and 97,0% were male. Traditional production was dominant among the small ruminant producers and as the number of animal increases the income increases ( p< 0,01). Out of twelve independent variables, eight of them were statistically significant on multiple linear regression analysis. The F-statistics was statistically significant at 1% level on communication behavior and animal health practices; 5% level on age, breeding reasons, milking way, produced products and fold type. The coefficient of multiple determination (R2) value was estimated to be 0,470 this implies that 47,0% of total variation in the output of small ruminant production was accounted for by the independent variables that were fitted into the model. The main problems of small ruminant production were high feed prices, high deaths of lamps/goat, insufficient use of pastures because of security problems and lack of shepherd due to young people unwillingness to live in rural areas.